KEEFEKTIFAN MODEL PROBLEM BASED LEARNING (PBL) TERHADAP PENINGKATAN KEMAMPUAN BERPIKIR KRITIS DAN PENGUASAAN KOMPETENSI MINIMUM MATERI GAYA KELAS IV SEKOLAH DASAR - Ghufron; Arbarini, Mintarsih; Suminar, Tri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research was motivated by the need for an effective learning model to improve critical thinking skills and students' mastery of minimum competencies, particularly in science subjects at the elementary school level. Conventional teaching methods remain dominant, leading to less active participation and limited critical thinking practice. This study aims to analyze the effectiveness of the Problem-Based Learning (PBL) model in enhancing critical thinking skills and mastery of minimum competencies on the topic of force in fourth-grade elementary students. This quantitative research employed a quasi-experimental method with a Nonequivalent Control Group Design. Data collection techniques included tests, observations, and documentation. Data were analyzed using normality tests, homogeneity tests, T-tests, and N-Gain tests. The study involved 50 fourth-grade students from SDN Bulusari 02 and SDN Rancawuluh 02, divided into experimental and control groups. The results showed that the PBL model significantly improved critical thinking skills and minimum competency mastery. The experimental group had a higher average pretest-to-posttest score increase than the control group. The T-test showed a significance value of 0.000 < 0.05, indicating a significant difference. N-Gain tests revealed improvements of 0.62 in critical thinking and 0.63 in minimum competency mastery, both in the moderate category. These findings suggest that Problem-Based Learning is effective in enhancing critical thinking and competency mastery.